Emotional Intelligence and Self-Control at Spread of Hoax News on Student Gadget Users - Wawan Agung Prastiyo; Ferdy Muzzamil; Arfian (Linguanusa : Social Humanities, Education and Linguistic, 2023)
Gadgets are technological products that can present various news media, social networks, entertainment, etc. Gadget users with low self-control tend to be easily exposed to hoax news, while a hoax itself is information engineered to cover up accurate information. Self-control can be influenced by one's emotional intelligence to determine and adapt to managing all forms of communication. Research This aims to know if emotional intelligence influences self-control on the spread of hoax news gadget users at " X " University students. This research method uses a quantitative approach, with data collection methods by giving a Likert scale to the research sample. The data collection technique used is purposive sampling, with samples research as many as 200 students. Data were analyzed using SPSS version 22 with a regression test. The results of this study indicate that the output R² (R Square) is 0.639, which means that emotional intelligence has a 63.9% influence on self-control in the spread of hoax news by gadget users at "X" University students. The conclusion of this study is intelligence emotions affect controlthemselves in the space of hoax news user gadgets student University "X." The higher the emotional intelligence , the higher the self-control.